2012
DOI: 10.1155/2012/628635
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Dendritic Cells as a Possible Mechanism of Negative Regulation of T Lymphocytes in Pulmonary Tuberculosis

Abstract: The PD-1/B7-H1-mediated induction of T cell apoptosis/anergy as a possible mechanism of immune response failure was studied in 76 patients with pulmonary tuberculosis (TB) with normal and low-proliferative response to antigens of M. tuberculosis (purified protein derivative (PPD)). It was revealed that dendritic cells (DCs), generated in vitro from patient blood monocytes with GM-CSF + IFN-α, were characterized by increased B7-H1 expression, upproduction of IL-10, and reducing of allostimulatory activity in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…The data obtained are consistent with those of Rajashree et al, which studied monocyte-derived DCs generated in presence of GM-CSF and IL-4 and found the inhibition of DC differentiation/maturation in pulmonary TB patients [18]. Besides, we for the first time have demonstrated that patient DCs had the increased expression of B7-H1 (PD-L1), known to induce T cell apoptosis and anergy upon interactions with PD-1 on T-cells [23]. The impairment of IFN-DC differentiation/activation in TB patients was associated with marked DCs dysfunction, in particular with altered cytokine production, decreased allostimulatory activity and the shift toward T2-stimulatory activity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The data obtained are consistent with those of Rajashree et al, which studied monocyte-derived DCs generated in presence of GM-CSF and IL-4 and found the inhibition of DC differentiation/maturation in pulmonary TB patients [18]. Besides, we for the first time have demonstrated that patient DCs had the increased expression of B7-H1 (PD-L1), known to induce T cell apoptosis and anergy upon interactions with PD-1 on T-cells [23]. The impairment of IFN-DC differentiation/activation in TB patients was associated with marked DCs dysfunction, in particular with altered cytokine production, decreased allostimulatory activity and the shift toward T2-stimulatory activity.…”
Section: Discussionsupporting
confidence: 91%
“…From this point of view, the prevalent T2-stimulating activity of IFN-DCs we have found in patients with active TB and especially in PPD-anergic patients, suggests that the DC alterations may be the cause of Th1 deficiency in pulmonary tuberculosis. Generally, the decreased allostimulatory activity, the dominance of T2 stimulating activity and the increased production of IL-10 along with our previous data on pro-apoptogenic activity of patient DCs [23], give evidence of "tolerogenic" phenotype of monocyte-derived DCs in TB infection. The engagement of PD-1/ PD-L1 (B7-H1) signaling pathway in DC cytotoxic activity was also demonstrated during tumor growth and in virus infections [28,30].…”
Section: Citationsupporting
confidence: 73%
“…The ability of DCs to kill target cells that could serve in anti-tumor immunity or T-cell killing in autoimmunity and transplantation has been described (Chauvin and Josien, 2008). A recent study in pulmonary tuberculosis patients confirms the cytotoxic activity of DCs as a mechanism of negative regulation of T lymphocytes (Sakhno et al, 2012). In case of VD3-DCs, this action is antigen-dependent but not restricted to naïve T cells since VD3-DCs also block IFNγ and IL-10 production and induce active killing of a diabetogenic Th1 clone in an antigen-specific manner (van Halteren et al, 2002).…”
Section: Killing Of T Cells By Tolerogenic Dcs – the Story Of Mr Andmentioning
confidence: 77%
“…Despite their seemingly preferential tumor-directed action, under certain circumstances, MoDCs can induce T cell death [21,32,37]. This observation was made in several studies ( Table 1); all of which were performed in the context of infectious diseases [21,32,37]. The first study demonstrated that MoDCs infected with measles virus can induce paracrine killing of autologous T cells [19].…”
Section: Killer Dcs In Humansmentioning
confidence: 99%
“…Conversely, another study found that CD40 ligation inhibits TRAIL expression in MoDCs, but the cytotoxic ability of these CD40L-matured MoDCs was preserved, suggesting TRAIL-independent mechanisms for induction of cell death [28]. Indeed, as outlined in Table 1, both cell contact-dependent and -independent mechanisms have been implicated in MoDC-mediated killing and their cytolytic armamentarium includes, in addition to TRAIL, a broad range of cytotoxic effector molecules such as TNFa [21][22][23][24]29,30], FAS-L [20][21][22]29,31,32], caspase-8 [19,[33][34][35], lymphotoxin (LT)-a1b2 [29], TNF-like weak inducer of apoptosis (TWEAK) [21], IFN-g [28], granzyme B [27,36], and programmed death ligand (PD-L1/2) [32,37].…”
Section: Killer Dcs In Humansmentioning
confidence: 99%